2009
DOI: 10.1182/blood.v114.22.507.507
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Activity of the OCT-1 Protein Is Predictive of Molecular Response and Survival in CP-CML Patients Treated with Imatinib: A 5 Year Update of the TIDEL Trial.

Abstract: 507 The major active influx protein for imatinib into target BCR-ABL positive cells is the organic cation transporter OCT-1. We have previously demonstrated that the functional activity of the OCT-1 protein (OCT-1 activity) is predictive of molecular response in TIDEL (trial of imatinib 600 mg/day with selective dose intensification in untreated CP-CML) The OCT-1 activity (OA) is measured in mononuclear cells from untreated CML patients by calculating the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…11 OCT1 activity was shown to predict overall survival and TKI response in CML patients. 12,13 Some studies showed that its gene expression predicts TKI response 14 pp 1,15 but the results could not be reproduced in several other studies. 16,17 Thus, this correlation is still a matter of debate.…”
Section: Introductionmentioning
confidence: 99%
“…11 OCT1 activity was shown to predict overall survival and TKI response in CML patients. 12,13 Some studies showed that its gene expression predicts TKI response 14 pp 1,15 but the results could not be reproduced in several other studies. 16,17 Thus, this correlation is still a matter of debate.…”
Section: Introductionmentioning
confidence: 99%